ASTM assessment of a novel shoulder prosthetic design: measurement of glenoid edge motion in three degrees of freedom - Haworth, Leanne (Department of Human Biology, 2025)
The most common cause for failure of An anatomical shoulder joint prosthesis is loosening of the glenoid component, widely attributed to ‘rocking' of the component under eccentric edge loading. The American Society for Testing and Materials (ASTM) set out a standardised test to evaluate glenoid loosening, in which the glenoid is cyclically loaded (for 100,000 cycles) and the vertical displacement of the edges is measured. However, under load the glenoid edges will also deflect horizontally and with a tilting motion. Therefore, the standardised test provides limited information regarding the glenoid behaviour. To measure the complex motions of the glenoid edges, an ASTM conforming test rig was designed and then augmented with a novel edge motion measurement system. The edge motion measurement system uses LVDT sensors to track the motion of rigid blocks on the end of lever arms connected to the glenoid edges. The block's motion is converted to complex glenoid edge motion using a MATLAB algorithm based on the system geometry. The test rig and edge motion measurement system were functionally validated in preliminary tests. The augmented test rig was then used to evaluate a novel glenoid design compared to an established (5-peg cemented) control glenoid. Six samples of each design were tested, and the resultant motion vectors were statistically compared using 1-dimensional statistical parametric mapping. The design intention of the novel glenoid was to decrease the edge motion by centralising the stresses experienced using gaps in the component surface. However, the experimental results showed increased edge motion on the novel glenoid, which was statistically significant (P<0.05) in the vertical and tilting directions. Observation of overall trends in the glenoid edge motion showed that rather than rocking, a downward and outward deformation of the edges occurs (usually within 5000 cycles). This deformation was further noted to not be a permanent effect, resulting in a time-dependent relaxation of the edges out of their deformed state, which contributes to the edge motion in tension. This contribution is believed to be non-trivial with respect to the overall motion and is likely why the novel glenoid results were counter to what was expected from the FEM. Overall, the key finding from this thesis was that the deformation and strain recovery of the glenoid components played a larger role in edge motion than the expected ‘rocking' and this observation should be accounted for when developing new glenoid designs.